Extranodal Diffuse Large B-Cell Lymphoma of the Small Bowel in Female Patient Causing Intestinal Obstruction: A Case Report - Nikolovski, Andrej; Trajkova, Sanja; Dukovski, Dushko; Spirov, Goran; Petrushevska, Gordana (Lietuvos chirurgija, 2022)
Diffuse large B cell lymphoma is the most common extranodal non-Hodgkin lymphoma of the small intestine accounting for more than 50% of cases. Forty percent of these cases initially present with small bowel obstruction. Therefore, the diagnosis is usually established after surgery for bowel obstruction. The treatment is then continued with a certain chemotherapy regimens. We present a case of a 46-years-old female patient with signs of small bowel obstruction due to previously undiagnosed diffuse large B-cell lymphoma. Postoperatively, the patient was treated with 7 cycles of R-CHOP protocol and complete response was achieved in the short follow-up period.